2018
DOI: 10.1093/jisesa/iey041
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of In Vivo Electroporation on the Delivery of Molecular Agents into Aphid (Hemiptera: Aphididae) Ovarioles

Abstract: While the wealth of genomic data presently available is increasing rapidly, the advancement of functional genomics technologies for the large majority of these organisms has lagged behind. The Clustered Regularly Interspaced Palindromic Repeats (CRISPR)/Cas9 system is an emerging gene-editing technology derived from a bacterial adaptive immune system that has proven highly effective in multiple model systems. Here, the CRISPR/Cas9 system was delivered into the ovarioles of the pea aphid, Acyrthosiphon pisum (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The feasibility of the application of in-vivo electroporation and viral transduction in insect species where a genetic tool kit is not available has been demonstrated in several recent studies. For example, to deliver CRISPR/Cas9 [ 36 ] or RNAi [ 37 ] vectors by in vivo electroporation or for the optogenetic manipulation of neurons by viral transduction [ 38 ]. Species specific differences, like the cellular density of a tissue or the expression of surface receptors, are one of the factors influencing the outcome of a physiological manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of the application of in-vivo electroporation and viral transduction in insect species where a genetic tool kit is not available has been demonstrated in several recent studies. For example, to deliver CRISPR/Cas9 [ 36 ] or RNAi [ 37 ] vectors by in vivo electroporation or for the optogenetic manipulation of neurons by viral transduction [ 38 ]. Species specific differences, like the cellular density of a tissue or the expression of surface receptors, are one of the factors influencing the outcome of a physiological manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…An important topic for future research is the contribution of the various candidate aphid genes identified in this study to the regulatory circuits that influence the EAA nutritional phenotype of the insect. Such future studies will be facilitated by ongoing innovations in methods to manipulate aphid genomes (Jamison, Thairu, & Hansen, ; Le Trionnaire et al, ), as well as expanded effort to identify candidate genes. In particular, full genome sequencing is predicted to yield further SNPs of interest, beyond those obtained in this study by the reduced‐representation genome sequencing by GBS.…”
Section: Discussionmentioning
confidence: 99%
“…The Clustered Regularly Interspaced Short Palindromic Repeat (CRISPR)-based genome editing system can be applied to various species, including non-model insects, which is crucial to develop novel pest control strategies [ 1 ]. To date, single guide ribonucleic acid (sgRNA)–Cas9 (CRISPR associated protein 9) ribonucleoprotein (RNP) complexes have been attempted to be delivered using DNA electroporation targeting the Target of Rapamycin ( Tor ) gene in viviparous aphid ovaries, with no indel mutations detected in the target gene in the offspring of treated individuals [ 2 ]. Although the CRISPR/Cas9 system has been tested in aphids, its deployment is still challenging due to the difficulty of injecting into aphid embryos because oogenesis occurs without apparent vitellogenesis.…”
Section: Introductionmentioning
confidence: 99%